2014
DOI: 10.21831/cp.v3i3.2378
|View full text |Cite
|
Sign up to set email alerts
|

Kemajuan Belajar Siswa Pada Geometri Transformasi Menggunakan Aktivitas Refleksi Geometri

Abstract: Abstrak: Penelitian ini bertujuan untuk mendeskripsikan kemajuan belajar siswa pada materi geometri transformasi yang didukung dengan serangkaian aktivitas belajar berdasarkan Pendidikan Matematika Realistik Indonesia. Penelitian didesain melalui tiga tahap, yaitu tahapan perancangan desain awal, pengujian desain melalui pembelajaran awal dan pembelajaran eksperimental, dan tahap analisis retrospektif. Dalam penelitian ini, Hypothetical Learning Trajectory, HLT (HLT) berperan penting sebagai desain pembelajara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
1
7
0
5
Order By: Relevance
“…This is because geometric transformation material requires high-level thinking. This is in line with three main reasons why students should learn the transformation geometry proposed by Hollebrands (Albab et al, 2014), which gives students the opportunity to think about important mathematical concepts (such as symmetry, functions, etc. ), providing a context that is make students think that transformation geometry involves various disciplines, and allows students to engage in activities that use higher-order thinking in many ways.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…This is because geometric transformation material requires high-level thinking. This is in line with three main reasons why students should learn the transformation geometry proposed by Hollebrands (Albab et al, 2014), which gives students the opportunity to think about important mathematical concepts (such as symmetry, functions, etc. ), providing a context that is make students think that transformation geometry involves various disciplines, and allows students to engage in activities that use higher-order thinking in many ways.…”
Section: Introductionsupporting
confidence: 69%
“…One of the mathematical material that has an important role in the development of student mathematics is the material of geometry transformation. as the opinion of Edwards (Albab, Hartono, & Darmawijoyo, 2014) which revealed that learning geometry transformation provides opportunities for the development of spatial visualization abilities and geometrical reasoning so that mathematical proofing abilities are obtained by students. Geometry transformation material is taught to the ninth grade students of junior high school (SMP), which is the uppermost grade level at the junior high school level.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, materials and learning methods can also be designed in such a way that the learning to make learners can think critically and reasoning. Some RME study design studies such as transformation geometry learning design (Albab, Hartono, & Darmawijoyo, 2014). Moreover Collaborative learning methods by comparing other students' answers have also been exemplified to begin this improvement (Albab, Saputro, & Nursyahidah, 2017).…”
Section: Problem Solving-related Critical Thinkingmentioning
confidence: 99%
“…Transformasi merupakan pengetahuan yang penting dalam geometri untuk membangun kemampuan spasial, kemampuan penalaran geometri, dan memperkuat pembuktian matematika (Edward dalam Albab et al, 2014). Beberapa kemampuan tersebut terbukti dapat menunjang pencapaian pada matematika, terutama penalaran terkait geometri transformasi.…”
Section: Pendahuluanunclassified